2007
DOI: 10.1111/j.1742-1241.2006.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Postchallenge hyperglycaemic spike associate with arterial stiffness

Abstract: Several large-scale epidemiological and intervention studies strongly indicate that postchallenge hyperglycaemia is the main factor associated with increasing the risk of morbidity and mortality in type 2 diabetes. However, the mechanisms that increase the risk of cardiovascular disease remain unclear. We aimed to study the relationship between postchallenge hyperglycaemia and arterial stiffness. We recruited 40 healthy subjects from a physical examination in 2005. Cardio-ankle vascular index (CAVI) was automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 28 publications
5
39
2
Order By: Relevance
“…While group diVerences were not observed, the meal test did elicit an increase in central arterial stiVness. Previous studies reported that arterial stiVness is associated (»r = 0.33) with hyperglycemia during an OGTT (Huang et al 2007;Ohshita et al 2004). We also observed an association between glucose concentrations and central PWV (r = 0.37, P < 0.001), despite the use of diVerent techniques to assess arterial stiVness.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…While group diVerences were not observed, the meal test did elicit an increase in central arterial stiVness. Previous studies reported that arterial stiVness is associated (»r = 0.33) with hyperglycemia during an OGTT (Huang et al 2007;Ohshita et al 2004). We also observed an association between glucose concentrations and central PWV (r = 0.37, P < 0.001), despite the use of diVerent techniques to assess arterial stiVness.…”
Section: Discussioncontrasting
confidence: 44%
“…The exact mechanism for arterial dysfunction in persons with impaired glucose tolerance is currently debated (Cosentino et al 1997(Cosentino et al , 2003Edwards et al 2004). Elevated glucose concentrations following an oral glucose tolerance test (OGTT) are strongly associated with increased arterial stiVness in populations that have both normal and impaired glucose tolerance (Huang et al 2007;Ohshita et al 2004), suggesting that acute physiological (postprandial) hyperglycemia may have a detrimental eVect on arterial function. Endothelial function was observed to be decreased 1 and 2 h after administration of an OGTT to individuals with impaired glucose tolerance (Kawano et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…CAVI and ABI for each participant were conducted at least twice. The test-retest reliability of CAVI and ABI in the Taiwanese population has been demonstrated as excellent [24].…”
Section: Methodsmentioning
confidence: 93%
“…8,12 CAVI is essentially independent of changes in BP during examination, but shows a strong correlation with systolic BP (SBP). 12 Although there are several reports of the evaluation of CAVI in patients on hemodialysis, 12 those with hyperglycemia 13 and those who had undergone heart transplantation, 14 there are few on the evaluation of CAVI as a screening tool for atherosclerosis in the general population, 11 and none about the correlation between CAVI and CIMT. Although we recently evaluated the availability of CAVI as a screening tool for atherosclerosis in young Japanese adult (mean age 21.4 years, range 18-31 years), no correlation was observed with other existing markers, including CIMT.…”
mentioning
confidence: 99%